Analysis of cross sections using various nuclear potential - Aziz, Azni Abdul; Kassim, Hasan Abu; Yusof, Norhasliza; F., Muhammad Zamrun (2014)
The relevant astrophysical reaction rates which are derived from the reaction cross sections are necessary input to the reaction network. In this work, we analyse several theoretical models of the nuclear potential which give better prediction of the cross sections for some selected reactions.